Proceedings of Corfu Summer Institute 2019 "School and Workshops on Elementary Particle Physics and Gravity" — PoS(CORFU2019) 2020
DOI: 10.22323/1.376.0135
|View full text |Cite
|
Sign up to set email alerts
|

Quintessence from higher curvature supergravity

Abstract: In this contribution we revisit higher curvature N=1 supergravity and discuss the quintessence phase that can appear due to the R 4 terms. In particular we focus on the bosonic supersymmetric completion within the old-minimal and the new-minimal formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The A i are the complex scalars that belong to the chiral superfields i . Models and discussions for quintessence in supergravity and in string theory can be found for example in [8,[22][23][24][25][26][27][28][29][30][31][32], a general review focused on string theory models can be found in [33] (and in [7]), and some alternative proposals in string theory can be found in [32,34,35]. Therefore we will not commit ourselves here to finding an appropriate superpotential P( i ) that gives to V SU G R A the required quintessence form.…”
Section: Examples In N = 1 Supergravitymentioning
confidence: 99%
See 1 more Smart Citation
“…The A i are the complex scalars that belong to the chiral superfields i . Models and discussions for quintessence in supergravity and in string theory can be found for example in [8,[22][23][24][25][26][27][28][29][30][31][32], a general review focused on string theory models can be found in [33] (and in [7]), and some alternative proposals in string theory can be found in [32,34,35]. Therefore we will not commit ourselves here to finding an appropriate superpotential P( i ) that gives to V SU G R A the required quintessence form.…”
Section: Examples In N = 1 Supergravitymentioning
confidence: 99%
“…31) which means to find the canonical χ T interactions we have to rescale (4.30) with k(τ ). Then from the consistency of the slow-roll phase one expects to have k(τ ) ∼ 10 −80 , (4.32) which means we have to redefine the fermion χ T as χ T ∼ 10 40 χ T | norm .…”
mentioning
confidence: 99%